(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The rise in the numbers of terrorist incidents, notably in recent years, has demonstrated that the impact of explosive loads on buildings must be taken into account in the design phase. Although this is exceptional, man-made catastrophes are in particular, blast loads are complex loads, which must be measured as earthquake and wind loads. The purpose of this study is to illustrate the hypotheses of blast resistant buildings, to improve the protection of buildings against explosives, and to establish construction strategies to counteract explosive impact. Firstly, explosives and forms of blasts is briefly described.